2017
DOI: 10.4236/ojmi.2017.74017
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Orthodontic 3D Printed Retainers versus Thermoformed Retainers

Abstract: Background: The integration of the current technology of CBCT and 3D CAD/CAM technology has great potential in the field of orthodontics, which is not yet fully investigated. The purpose of this article is to evaluate the accuracy of 3D printed retainers in comparison to vacuum formed retainers. Methods: Alginate impressions were taken for ten patients who have a CBCT scan. A 3D printed retainer and vacuum formed retainer were fabricated. Linear measurements were measured by two assessors using digital caliper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
0
21
0
2
Order By: Relevance
“…A few years later, the same authors evaluated the fit of the 3D-printed retainers. 21 In that study, digital calipers were used to measure the difference between the 3D-printed retainer and a vacuum-formed retainer. In the present study, software was used to superimpose the digital images of the printed retainers and their original models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years later, the same authors evaluated the fit of the 3D-printed retainers. 21 In that study, digital calipers were used to measure the difference between the 3D-printed retainer and a vacuum-formed retainer. In the present study, software was used to superimpose the digital images of the printed retainers and their original models.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by the same investigators reported that the 3D-printed retainers were as accurate and reliable as the traditional vacuum-formed retainers. 21 However, comparisons between the 2 retainers were made based on the linear measurements performed manually with the use of digital calipers. Furthermore, the digital file used to fabricate the retainers was created from a CBCT image.…”
mentioning
confidence: 99%
“…A recent study compared the accuracy between orthodontic 3D printed and thermoformed retainers, in which 3D printed retainers were reported as more accurate and reliable than the conventional vacuum formed retainer [35]. Based on this study, it is important to note that CBCT was used to create the digital file to fabricate the two retainers.…”
Section: Review On Accuracymentioning
confidence: 99%
“…In 2014, a selective laser sintering (SLS) 3D printer was successfully used to fabricate a retainer directly from a digital model of cone-beam computed tomography (CBCT) without a physical model, as reported by Nasef, El-Beialy, and Mostafa. [35] Although the accuracy of fabricated retainer appliances was not assessed, the 3D printing technologies using CBCT provided simplicity, accuracy, speed, and patient satisfaction. The study results indicated 3D virtual retainer with user-friendly software seemed to be a promising technique that would eventually change the practices in present-day dentistry.…”
Section: Review On Accuracymentioning
confidence: 99%
See 1 more Smart Citation